Análise comparativa de dois livros didáticos de língua japonesa: um estudo sobre as dez primeiras lições do Minna no Nihongo Shokyû I (2° Edição) e Irodori (Introdutório A1) - Mendonça, Paulo Victor de Sena (Brasil, 2023)
This study on the comparative analysis of two Japanese language textbooks takes into consideration the importance of using the textbook in the teaching-learning process, which, many times, because it is considered a “resource par excellence”, an exclusive source of knowledge, teachers and students limit themselves to not developing the various aspects of the language under study. In this context, we seek to analyze and compare the textbook and audio files of the first ten lessons of Minna no Nihongo Shokyû I (2nd Edition) and Irodori (Introductory A1), in which we analyze the information and construction of the lessons in the textbooks, the teaching methods, linguistic skills and language of the two books, with a theoretical basis in the studies of Alkmin (2001), Coracini (1999), Feldmann (2019), Ferro and Bergmann (2013), among others. It was found that, although the textbooks are of basic level, the objectives are the opposite and therefore, we found that the teaching methods are different, each book develops the activities focusing on a certain linguistic skill and the language does not expose the students enough to the various ways that language is presented within a society, linguistic variations. In addition to this analysis, we brought a critical reflection on the importance of the use these textbooks within the classroom.